ANALISIS PEMASARAN USAHA GULA AREN DI DESA BABANA KECAMATAN BUDONG-BUDONG KABUPATEN MAMUJU TENGAH - Rahmah, ST; Kassa, Saharia; Khatima, Husnul (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
The research aimed to determine the various channels and mechanisms of the marketing dynamic of palm sugar. It was conducted from August to September 2021 in Babana Village, Budong Budong Subdistrict, Mamuju Central District, engaging with a total of 32 palm sugar craftsmen selected using a simple random sampling method. The findings reveal a complex network of marketing channels, with two primary routes: (i) the first channel involves selling palm sugar to collectors, who then resell it to wholesalers in Mamuju Central city, before finally reaching consumers outside the city (West Kalimantan) and (ii) the second channel involves direct sales from the craftsmen to wholesalers, who then distribute the product to consumers in West Kalimantan. The analysis also indicated significant differences in marketing margins between these two channels, with a margin of IDR 5,000/kg in the first channel and of IDR 3,000/kg in the second. A higher percentage (88%) of the final price were received by the craftsmen in the second channel than the first channel (80%). The second channel is more efficient with 80% efficiency value compared to 42% in the first channel.